2023
DOI: 10.1007/s00125-023-05962-z
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic aspects of incretin-based therapy

Abstract: Incretin-based therapies, particularly glucagon-like peptide-1 receptor agonists (GLP-1 RAs), have demonstrated cardiovascular benefits in people with type 2 diabetes. However, socioeconomic disparities in their uptake may constrain the collective advantages offered by these medications to the broader population. In this review we examine the socioeconomic disparities in the utilisation of incretin-based therapies and discuss strategies to address these inequalities. Based on real-world evidence, the uptake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Changes in body mass usually took place among marginal side effects of inappropriate diet and lifestyle [17]. On the other hand, changes of current amount of adipose and muscle tissues in the body are associated with availability of endogenous and/or injected insulin along with production of incretins in gut or their therapeutic administering and/or the sensitivity of respective receptors [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in body mass usually took place among marginal side effects of inappropriate diet and lifestyle [17]. On the other hand, changes of current amount of adipose and muscle tissues in the body are associated with availability of endogenous and/or injected insulin along with production of incretins in gut or their therapeutic administering and/or the sensitivity of respective receptors [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hyperglycemia is supported by escalated activity of SGLT2 in kidneys, resulting in increased reabsorption of glucose from primary urine. So, euglycemia, optimal body mass and normal lipoproteinemia may be regulated using insulin and/or incretin preparations and/or gliflozins and other medication without delay [16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is essential to consider the broader implications of adopting these therapies in real-world settings, particularly concerning their cost. Observational data suggest a notable under-utilisation of GLP-1 RAs among individuals in lower socioeconomic groups, primarily due to the high cost of these medications, highlighting the disparity in access to effective diabetes treatments based on socioeconomic factors [ 63 ]. From a broader societal perspective, even though s.c. tirzepatide has been suggested to be cost-effective compared with s.c. semaglutide in the USA [ 64 ], cost-effectiveness analyses conducted in low-, middle- and high-income countries have demonstrated that GLP-1 RAs are not cost-effective compared with other glucose-lowering drugs [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the availability and uptake of incretin-based therapies depend highly on socioeconomic disparities and currently cannot address the full scale of the obesity pandemic. 264,265 Thus, it remains of paramount relevance to further develop new approaches to behavioural therapy and to create innovative incentives to engage people in a healthy lifestyle.…”
Section: Adverse Effects Treatment Adherence and Persistence Of Glp-1...mentioning
confidence: 99%